2016
DOI: 10.1038/srep28941
|View full text |Cite
|
Sign up to set email alerts
|

An ABA-increased interaction of the PYL6 ABA receptor with MYC2 Transcription Factor: A putative link of ABA and JA signaling

Abstract: Abscisic acid (ABA) is a plant hormone that mediates abiotic stress tolerance and regulates growth and development. ABA binds to members of the PYL/RCAR ABA receptor family that initiate signal transduction inhibiting type 2C protein phosphatases. Although crosstalk between ABA and the hormone Jasmonic Acid (JA) has been shown, the molecular entities that mediate this interaction have yet to be fully elucidated. We report a link between ABA and JA signaling through a direct interaction of the ABA receptor PYL6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 85 publications
4
109
0
1
Order By: Relevance
“…S5B, and Dataset S7). These results point to a possible connection between ABA and JA signaling pathways via an ABA receptor (45). However, the other pairs tested by Y2H assay, such as TGA1-PYL6 and ABI5-PYL6, showed no interaction (SI Appendix, Fig.…”
Section: Halotag-nappa Reveals a Potential Role Of Tfs In Plant Hormonementioning
confidence: 73%
“…S5B, and Dataset S7). These results point to a possible connection between ABA and JA signaling pathways via an ABA receptor (45). However, the other pairs tested by Y2H assay, such as TGA1-PYL6 and ABI5-PYL6, showed no interaction (SI Appendix, Fig.…”
Section: Halotag-nappa Reveals a Potential Role Of Tfs In Plant Hormonementioning
confidence: 73%
“…The role of PYL8 in regulating lateral root growth is independent of the core ABA signaling pathway, because PYL8 directly interacts with MYB77, and this ABA-induced interaction enhances MYB77-dependent transcription of auxin-responsive genes (Zhao et al, 2014). Similarly, PYL6 interacts with MYC2, a key transcription factor in jasmonate responses, and thus connects ABA and jasmonate pathways (Aleman et al, 2016). Single-gene mutations in most other PYLs do not result in drastic ABA phenotypes.…”
Section: Aba Signalingmentioning
confidence: 99%
“…It was recently shown that the ABA receptor, PYR6, interacts with MYC2. This suggests a close interaction between the ABA and JA pathways (Aleman et al, 2016). ABI5 also seems to participate in the ABA-JA crosstalk.…”
Section: Abi5 As the Integrator Of Aba And Other Phytohormone Signalimentioning
confidence: 99%